Review of 17 Cases of Pneumonia Caused by Streptococcus pyogenes - Barnham, M. (Eur J Clin Microbiol Infect Dis, 1999)
Streptococcus pyogenes is an uncommon cause of community-acquired pneumonia and there have been few recent specific accounts of the condition. To describe the current nature of this disease in the UK, data was gathered on patients with clinical pneumonia from whom Streptococcus pyogenes was cultured principally from blood or other relevant normally sterile sites. In the Harrogate and Northallerton districts of North Yorkshire, pneumonia accounted for nine (20%) cases and a quarter of all deaths in a complete sequence of 45 patients with Streptococcus pyogenes bacteraemia detected during the 16-year-period 1981–1996. An analysis is presented of those cases together with eight recent cases from counties York, Durham and Isle of Wight during 1995–1997. Of the total 17 cases, nine occurred in women and eight in men; the age range was 30–92 years. The organism was isolated from blood culture in 15 (88%) patients. Eight (47%) patients died, five within 1 day of hospitalisation. Fourteen (82%) cases occurred in the winter months October to March, including all the fatal cases and all eight in which a clinical 'viral' prodrome was observed. Predisposing medical or surgical conditions were present in 65% of the patients. Major complications included septicaemia, pleural reaction, shock, pulmonary cavitation, osteomyelitis and metastatic abscesses. Seven serotypes of Streptococcus pyogenes were encountered, with M-type 1 predominating (the cause in 60% of cases). All infections were community acquired; two small clusters of fatal pneumonia were seen.